Bounds on lifetime of cluster-based ultra-wide band wireless sensor network. (21st May 2008) - Xu, Juan; Hong, Yong-Fa; Jiang, Chang-Jun
The asymptotic lower and upper bounds on the lifetime of cluster-based Time-Hopping Impulse Radio Ultra-Wide Band (TH-IR UWB) wireless sensor networks with n static sensor nodes randomly located on a square of area S are considered. We derive the lower and upper bounds on the lifetime of cluster-based TH-IR UWB sensor networks. The results indicate that the lifetime of cluster-based network is Θ((n/S log n)α/2), which is at least (n1/2/(log n)α-1/2) times longer than that of non-cluster-based TH-IR UWB network; thus clustering can significantly improve the network lifetime. The bounds also reveal that the network lifetime increases with node density n/S, thus the large-scale dense cluster-based TH IR UWB wireless sensor network is more practical.